Assessing Relational Functioning in Couple and Family Therapy: A Comparative Analysis of Systemic Assessment Instruments in Psychotherapeutic Practice - Sava, Nicu-Ionel; Moldovanu, Ioana Diana; Boboc, Brigitte (New Trends in Psychology, 2026)
Assessing relational functioning is a core component of both clinical practice and research in couple and family therapy. Within systemic psychotherapy, assessment is understood as a theory-driven process that actively shapes clinical understanding, hypothesis formulation, and intervention planning. Despite the widespread use of systemic assessment instruments, considerable variability persists in their epistemological assumptions, methodological structure, and clinical utility. This article presents a comparative analysis of four widely used systemic tools—the genogram, the Fundamental Interpersonal Relations Orientation (FIRO) model, the Dyadic Adjustment Scale (DAS), and the Family Adaptability and Cohesion Evaluation Scales (FACES)—focusing on how each conceptualizes relational functioning and informs systemic case formulation. The analysis examines theoretical coherence, methodological characteristics, and the capacity of these instruments to capture dynamic and reciprocal relational processes. Findings suggest that no single instrument adequately reflects the complexity of couple and family relationships. Qualitative tools provide contextual and transgenerational depth, while standardized measures offer structural clarity and comparative rigor. Their integrative use supports more coherent clinical formulation and evidence-informed systemic practice.